2021
DOI: 10.1101/2021.04.14.21255358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of interventions to increase physical activity for people with heart failure: a meta-analysis

Abstract: Objectives This meta-analysis aims to 1) evaluate the efficacy of physical activity interventions in heart failure and 2) to identify intervention characteristics significantly associated with the interventions' efficacy. Methods Randomised controlled trials reporting intervention effects on physical activity in heart failure were combined in a meta-analysis using a random-effect model. Exploratory meta-analysis was performed by specifying the general approach (e.g. cardiac rehabilitation), strategies used (e.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Older age is a barrier to physical activity in HF, as suggested by both qualitative and quantitative evidence. This result further reiterated the finding of a meta-analysis (Amirova et al, 2021) that older adults living with HF need more support to attain higher physical activity levels.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Older age is a barrier to physical activity in HF, as suggested by both qualitative and quantitative evidence. This result further reiterated the finding of a meta-analysis (Amirova et al, 2021) that older adults living with HF need more support to attain higher physical activity levels.…”
Section: Discussionsupporting
confidence: 67%
“…Finally, tentative suggestions are made for what a future physical activity intervention needs to include Overall, the review findings indicate that to reduce the barriers and enhance the enablers, a behaviour change intervention containing the following BCTs are needed: identity associated with target behaviour, prompt/cues and adding objects to the environment, behavioural practice/rehearsal, and graded tasks. A previous meta-analysis of randomised controlled trials also suggested that these strategies are associated with the efficacy of interventions (Amirova et al, 2021). In addition, the qualitative evidence included in this review suggests that addressing the change in the social identity as a result of acquired HF diagnosis and the perceived appropriateness of physical activity in this context need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of RCTs reporting on the effects of PA among participants with HF found that the specific features indicative of a more successful intervention included a center-based group-oriented delivery format that combined exercise with behavioral change strategies. 62…”
Section: Physical Activity and Sedentary Behaviormentioning
confidence: 99%